276 The characterisation of dupuytrens disease in climbers. (3rd March 2020) - Jones, Gareth; Johnson, Mark; Woodards, Cara; Halsey, Tim
Abstract : Background: The risk of developing Dupuytrens disease—a benign chronic fibro-proliferative condition of the palmer fascia—has been associated with chronic heavy manual labour. The fingers and hands of climbers are routinely subjected to high load forces which may predispose individuals to disease development. The prevalence within the general population is unknown throughout the lifespan but has been found to increase with age and is estimated to be 12% at 55 yrs and 29% at 75 yrs. There is a paucity of information in regard of this condition in climbers. Objective: To characterise Dupuytren's disease in a large sample of active climbers. Design: Retrospective cross-sectional online survey utilising operational measures of disease, climbing behaviour and injury. Setting: Participants recruited via The Climber's Club of Great Britain and UKClimbing.com Patients (or Participants): 369 active climbers (307 male, 62 female) aged 14–80 Interventions (or assessment of risk factors): Climbing behaviours and key demographics. Main outcome measurements: Prevalence of Dupuytren's, injuries requiring medical assistance or withdrawal from participation for ≥1 day. Results: The prevalence of Dupuytren's was 17.6% (65/369). Of the 65 climbers (mean age 51.28 SD ± 13.77), 59 climbers were male (mean age 51.25 SD ±14.01) and 6 climbers were female (mean age 51.50 SD ± 12.37). Dupuytren's was present in 40 climbers bilaterally and 25 climbers unilaterally. The fourth and fifth fingers were the most commonly affected digits. The youngest climber diagnosed was 23 yrs and 38 climbers were diagnosed ≤ 55 yrs of age. Twenty-one climbers underwent surgery. Of these 19 had successful outcomes and 2 climbers had a recurrence. No climbers reported percutaneous needle fasciotomy or injection of collagenase as a clinical intervention. There was no increased risk of finger injury in Dupuytren's participants (RR 0.62 (95% CI, 0.43–0.89); OR 0.44 (95% CI, 0.25–0.77)). Conclusions: Dupuytren's does not appear to increase the risk of finger injury in climbers. A prospective study to investigate disease onset and progression in climbers is warranted.